Value-Based Governance and Islamic Entrepreneurship Education Practices for Strengthening Students’ Economic Independence - Widya Arif Sofyan Kurniawan; Thomas Stefanus Kaihatu; Timotius Febry Christian; Denny Bernardus (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the governance and value-based Islamic entrepreneurship education practices at Pondok Pesantren Al-Urwatul Wutsqo Jombang and their implications for strengthening students’ economic independence. Employing a qualitative case-study design, data were collected through in-depth interviews, participatory observation, and document analysis, and then thematically analyzed to obtain a comprehensive understanding of the pesantren’s entrepreneurial dynamics. The findings reveal that entrepreneurial governance is shaped through the integration of Islamic values, trustworthiness, honesty, discipline, and responsibility with an organized management structure and a deliberative decision-making mechanism (syura). The learning practices adopt experiential learning, where students are directly involved in production, marketing, and bookkeeping, enabling them to acquire technical skills while internalizing Islamic work ethics. Entrepreneurship education also enhances students’ self-confidence, communication abilities, and economic self-reliance. However, the study indicates that critical reflection and digital literacy remain underdeveloped, resulting in operational rather than strategic independence. This research contributes to strengthening value-based entrepreneurial models in Islamic boarding schools, yet its single-site focus limits it. Future studies should include comparative analyses across pesantren and explore the integration of digitalization within Islamic entrepreneurship frameworks.